Genetic studies of yield and quality traits in Indian mustard (Brassica juncea L.) - Ankit Patel,; KP Prajapati,; PJ Patel,; SK Shah,; PS Patel, (Journal of Oilseed Brassica, 2026)
To study the heterosis, combining ability and components of genetic variance for seed yield and 11 quantitative,and qualitative characters in 40 F1s of Indian mustard resulting from 10 lines and 4 testers along with standardcheck GM 3 were sown in a Randomized Block Design with three replications at Main Castor–MustardResearch Station, Sardarkrushinagar during Rabi 2012-13. Analysis of variance revealed the significantdifferences among genotypes for all the traits. The gca and sca variances were significant for all the traits.The ó2 gca and ó2 sca ratio indicated that non-additive gene action was predominant in the inheritance of allthe traits except, plant height and number of siliquae per plant. The parents SKM 0518, SKM 0907 and SKM0445 were good combiners for seed yield per plant. Besides among these parents SKM 0518 was also goodgeneral combiner for days to flowering, days to maturity, number of siliquae per plant, oleic acid, erucic acidand glucosinolate content. The estimates of sca effects indicated that the cross combinations SKM 0820 xGDM 4 (15.5) followed by SKM 0715 x SKM 0445 (13.5) and SKM 0907 x SKM 0445 (12.5) were significantfor seed yield per plant. The cross SKM 0820 x GDM 4 registered high per se performance, standardheterosis and sca effects for seed yield per plant. Considering mean performance, heterosis and combiningability effects, parents SKM 0518, SKM 1013, SKM 0445 and SKM 0904 and hybrids SKM 0820 x GDM 4,SKM 0907 x SKM 0445 and SKM 0715 x SKM 0445 were found promising for the development of highyielding genotypes. The results revealed that breeding approaches like biparental mating followed byrecurrent selection, diallel and line x tester selective mating design etc., are suggested to identify desirabletransgressive segregants for further improvement of these traits.